PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PERANGKAT DESA DENGAN KEPEMIMPINAN SEBAGAI VARIABEL MODERATING DI DESA BUGEMAN, DESA KENDIT, DESA BALUNG KECAMATAN KENDIT - Sucahyono, Syawal; Fandiyanto, Randika; Anshory, Muhammad Iqbal (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This research aims to determine the influence of the work environment and work discipline on the performance of village officials with leadership as a moderating variable in Bugeman village, Kendit village, Balung village, Kendit sub-district, Situbondo Regency. imi's research used a quantitative approach which was carried out by distributing questionnaires to 39 village officials in Bugeman village, Kendit village and Balung village, Kendit sub-district, Situbondo Regency. The data analysis method used in this research is multiple linear regression analysis. Hypothesis test results have a direct effect using the Smart PLS 3.0 application. Hypothesis test results show that the work environment has a significant effect on performance, work discipline has no significant effect on performance. The results of the hypothesis test with moderation of the leadership variable show that the work environment variable has a negative but significant effect on performance. The results of the hypothesis test with moderation of leadership show that the work discipline variable has a positive but not significant effect.